Multimorbidity of mental health and substance use disorders among housed and homeless U.S. veterans - Jack Tsai; Dorota Szymkowiak; Hind Beydoun (Scientific Reports)
Abstract Housing can be an important social determinant of mental health, which is why it is important to understand how mental health disorders (MHDs) and substance use disorders (SUDs) cluster and vary by housing instability. This study examined rates of comorbid MHDs and SUDs among three groups of U.S. veterans: those experiencing homelessness, those in supported housing, and those independently housed. Administrative data on a national cohort of 5,402,062 veterans (including 181,131 homeless veterans and 29,166 veterans in supported housing) enrolled in the U.S. Department of Veterans Affairs (VA) healthcare system from 2021 to 2023 were analyzed. Among homeless veterans, 28.3% had a SUD diagnosis, 62.9% a MHD diagnosis, and 24.7% comorbid MHD/SUD. Among veterans in supported housing, 38.2% had a SUD diagnosis, 67.3% a MHD diagnosis, and 32.0% comorbid MHD/SUD diagnoses. Among independently housed veterans, 7.9% had a SUD diagnosis, 41.6% a MHD diagnosis, and 5.8% comorbid MHD/SUD diagnoses. Homeless veterans with comorbid MHD/SUD used significantly more outpatient, inpatient, and emergency department care than veterans in supported housing; in turn, supported housing veterans with comorbid MHD/SUD used significantly more outpatient, inpatient, and emergency department care than independently housed veterans. Among homeless veterans with comorbid MHD/SUD diagnoses, those with addiction to central nervous system (CNS) stimulants used more outpatient, inpatient, and emergency department care than those with addiction to CNS depressants. In conclusion, the psychiatric epidemiology and comorbidity of veterans varies by housing situation, and there is continued need for psychiatric treatment among homeless veterans who enter supported housing.